Automated Generation of Training Programs for Swimmers Generating Weekly Training Plans in the Style of a Professional Swimming Coach Using Genetic Algorithms and Random Trees - Eriksson, Rikard; Nicander, Johan (My University, 2021)
Optimal training planning is a combination of art and science, and a task that requires expert knowledge. This is a time-consuming task that is often exclusively available to top tier athletes. Many athletes outside the elite do not have access or cannot afford to hire a professional coach to help them create their training plans. In this study, we investigate if it is possible to use the historical training logs of elite swimmers to construct detailed weekly training plans similar to how a specific professional coach would have planned. We present a software system based on machine learning and genetic algorithms for generation of detailed weekly training plans based on desired volume, intensity, training frequency, and athlete characteristics. The system schedules training sessions from a library extracted from training plans written by a professional swimming coach. Results show that the proposed system is able to generate highly accurate training plans in terms of training load, types of sessions, and structure, compared to the human coach.
Keywords: SWIMMING; TRAINING PLANNING; TRAINING PLAN GENERATION; MACHINE LEARNING; EXERCISE INTELLIGENCE